Convergence of complex multi-variables based on fading channels in multi-antenna communication systems - Pham Anh, Thu; Nguyen Duc, Minh; Le Hai, Chau; Minh, Hoang Trong (Vietnam Journal of Science and Technology, 2025)
This work introduces approximate expressions and provides comprehensive simulation results to demonstrate the robust convergence of complex variables based on fading channels in multi-antenna communication systems, in which two separate scenarios, namely spatial signal processing and non-spatial signal processing scenarios, were evaluated. Numerical results prove our assertions that for Nakagami-m and Rician fading channels (or can be extended to any other complex fading channels) in multi-antenna systems with antenna numbers larger than two, the distribution of interference from the beamforming design, a typical example for spatial signal processing, and will strongly converge to an exponential distribution with the scale-parameter remaining the same. Meanwhile, the channel synthesis in the non-spatial signal processing scenario tends to an exponential distribution with a new scale parameter exactly equal to the product of the number of antennas and the scale parameter.